(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2024)
Chronic kidney disease (CKD) constitutes a significant global health challenge, ranking among the foremost causes of morbidity and mortality. The effective management of CKD by primary care providers is imperative to mitigate the risk of complications, including cardiovascular disease, progression to end-stage renal disease (ESRD), and premature mortality. The integration of traditional approaches, such as Ayurveda, with conventional management strategies offers a comprehensive framework for CKD management. A 73-year-old male with a documented history of hypertension and a recent diagnosis of CKD Stage V presented to Jeena Sikho Lifecare Limited Hospital exhibiting symptoms such as pedal edema, periorbital swelling, and gastric disturbances. The patient underwent Panchakarma therapy, Ayurvedic medication, and lifestyle and dietary modifications. Substantial symptom relief was observed following the integrative treatment approach.